A Clinico-Pathological Multidisciplinary Team Increases the Efficacy of Skin Biopsy and Reduces Clinical Risk in Dermatology - Carlo Francesco Tomasini; Andrea Michelerio; Eugenio Isoletta; Stefania Barruscotti; Barbara Wade; Alba Muzzi (MDPI AG, 2023)
A clinical risk is an inherent risk in healthcare processes, including skin biopsy procedures, and may lead to misdiagnoses, increased healthcare costs and potential harm to patients. Indeed, clinical and histopathological data must be integrated if we are to reduce clinical risks and improve diagnostic accuracy in the diagnosis of dermatologic diseases. Although dermopathology services used to be part of a dermatologist's duty, the recent centralization of these laboratories has caused a loss of expertise and increased both complexity and safety issues. Some countries have implemented clinical-pathological correlation programs aimed at facilitating communication between clinicians and dermatopathologists. However, Italy has regulatory and cultural barriers that make the implementation of these programs difficult. Therefore, an internal analysis was carried out to assess the efficacy and impact that skin biopsy procedures for inflammatory and neoplastic conditions have on the quality of care in our dermatology department. As the analysis evidenced a high number of descriptive pathologic reports and discordant diagnoses, a multidisciplinary group of four dermatologists, four general pathologists and one dermatopathologist was set up. Herein, we present the results of this analysis and project and describe the structure of the multidisciplinary group. We also discuss the pros and cons, possibilities and limitations of our project, including the regulatory barriers of the Italian National Health System.